Air access liberalization, marketing promotion and tourism development. (20th November 2018) - Seetanah, Boopen; Sannassee, Raja Vinesh; Teeroovengadum, Viraiyan; Nunkoo, Robin
Abstract: This paper in the first place attempts to assess the impact of air access liberalization on tourism development for Mauritius and secondly goes on to analyse the dual impact of the interplay between air access liberalization and marketing promotion efforts as well. Using dynamic time series analysis, namely an Autoregressive Distributed Lag (ARDL) framework over the period 1970 to 2015, the results reveal that air access liberalization is an important element for tourism development. The findings also interestingly point to the positive and significant impact of the interplay between air access liberalization and marketing promotion efforts in attracting tourist.